«YOSHLIK» KONI MIS - MOLIBDEN RUDALARINI YANCHISH JARAYONINING XUSUSIYATLARI (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
For the sustainable development of the mineral raw material base, it is necessary to attract low-quality, off-balance and unconventional mineral resources for processing. This goal can be achieved by increasing the efficiency of extraction of valuable components, reducing energy and economic costs at the subsequent stages of enrichment and processing. The processes of preparing ores for enrichment are the most energy-intensive in mineral processing plants and have a significant impact on subsequent mineral processing processes. In order to optimize the processes of preparing copper-molybdenum ores for enrichment and to study the kinetics of crushing, some research was conducted on the ores of the "Yoshlik" deposit. To quantitatively assess the selectivity of ore preparation operations, the distribution of components by size classes was analyzed according to the results of elemental analysis and granulometric analysis.